Incidence of Intestinal Parasites in Government and Private School Going Children - Asim Fida, Muhammad Aslam, Bushra Samoon, Lata Kumari, Latif Najmi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Intestinal parasites not only pose a public health risk worldwidely, but also particularly prevalent in developing countries. They are among the least recognized infectious diseases in the world. The occurrence of intestinal parasites among children attending school is a matter of particular concern because they are at a critical stage of development, and their health can have a negative impact on their growth and academic performance. Study design: This cross-sectional study was conducted at Akhtar Saeed Medical College, Rawalpindi for duration of six months from September 2022 to February 2023. Material and Methods: Data from 25 private school children and 25 government school children was examined and it was found that there were 10 positive cases of intestinal parasites found among government school children and there were 4 cases positive among private school children. Results: The highest percentage of parasite that was found was E.histolytica (22%) followed by G.lamblia (19%). There were 8% cases where hookworm was found to be the cause of intestinal issues. Parasite distribution based on type of school showed that there were 71% cases positive cases found in the government sector schools whereas 28% positive cases were from the public sector schools Conclusion: This study analyzed the incidence of intestinal parasites in private and government school-going children and found that government school children are more exposed to unhygienic conditions leading to intestinal parasite infections. The study highlights the importance of addressing the underlying factors contributing to the high incidence of intestinal parasites in the region and underscores the need for a coordinated and sustained effort to tackle this public health issue. Keywords: intestinal parasite, sanitation, infection and school children.